Characteristics, wear and corrosion properties of borided pure titanium by pack boriding near α → β phase transition temperature. Issue 10 (July 2020) - Duan, Yonghua; Wang, Xinyu; Liu, Dan; Bao, Weizong; Li, Ping; Peng, Mingjun
Abstract: The boride layer characteristics, wear and corrosion properties of borided commercially pure titanium by pack boriding near the α → β phase transition temperature were investigated using X-ray diffraction, scanning electron microscopy, electron probe microanalysis, dry reciprocating friction tests, and electrochemical experiments in this work. The pack boriding was carried out at the temperatures of 860 °C, 880 °C, 900 °C, and 920 °C for 5, 10, 15 and 20 h. The results indicated that, in both α and β phase temperatures, the boride layer is composed of the outer TiB2 layer and the inner TiB layer. The α→β phase transition temperature of commercially pure Ti in this work is in the range of 882–900 °C, and the growth of TiB layer can be enhanced at this temperature range. Commercially pure Ti borided at 920 °C for 20 h has the best wear resistance and corrosion resistance. Finally, wear and corrosion mechanisms were also discussed.